Home-Court Advantage and Home Win Percentage in the NBA: An In-Depth Investigation by Conference and Team Ability - Adrián López-García; Enrique Alonso-Pérez-Chao; Rafael M. Navarro Barragán; Sergio L. Jiménez-Sáiz (Applied Sciences)
The National Basketball Association (NBA) is the major professional basketball league in the United States. Home-court advantage (HA) and home win percentage (HW) have been identified as decisive factors in determining the final outcome of a game. This study analyzes a total of 24 regular seasons, with two main objectives: (i) comparing HA and HW within the two conferences and (ii) examining the influence of team ability on HA and HW. HA (%) was calculated as (total home wins/total wins) × 100, and HW (%) as (total home wins/total home games) × 100. Teams were categorized into four different groups based on their season win percentage using cluster analyses. Regarding the first aim, we used an Independent Samples T-test and Mann–Whitney to assess differences between conferences. Subsequently, we evaluated the second objective using one-way ANOVA or Kruskal–Wallis. The results indicated no significant differences in HA within conferences. However, Western teams tended to have a higher HW than Eastern teams. The analyses revealed significantly higher HA in contender teams compared to the rest of the team abilities (p < 0.001). High–medium-ability teams also showed a significantly higher HA (p < 0.001) compared to low-ability teams. However, non-significant differences were found between the remaining groups for HA. Regarding HW, we observed significantly higher values in the contender teams compared to the teams with other ability levels (p < 0.001). Additionally, the high–medium-ability teams also exhibited significantly higher HW values (p < 0.001) when compared to the medium–low- and low-ability teams. Furthermore, the medium–low-ability teams showed significantly higher HW values (p < 0.001) when compared to the low-ability teams. Those findings suggest that team ability influences HA and HW in the NBA, where contender teams have significantly higher HW and HA values compared to the teams with other team ability levels. Understanding these dynamics provides valuable insights for team strategies, particularly during playoff stages where home-court advantage can be critical for success.